2022
DOI: 10.1186/s12883-022-02650-0
|View full text |Cite
|
Sign up to set email alerts
|

Neck-specific strengthening exercise compared with placebo sham ultrasound in patients with migraine: a randomized controlled trial

Abstract: Background Migraine patients have musculoskeletal disorders and pain in the cervical. And, despite the pathophysiology demonstrating the relationship between migraine and the cervical spine, the effectiveness of craniocervical exercises in these patients has not been verified. So, the aimed of this study was verify the effectiveness of craniocervical muscle-strengthening exercise (CMSE) in reducing the frequency and intensity of headache in migraine patients.  Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…However, more research regarding the effects of resistance training for migraine treatment is needed to reduce the uncertain evidence in these patients. Moreover, strengthening of the neck muscles appears to be ineffective for reducing migraine pain, obtaining a C grade of recommendation against this intervention ( Benatto et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more research regarding the effects of resistance training for migraine treatment is needed to reduce the uncertain evidence in these patients. Moreover, strengthening of the neck muscles appears to be ineffective for reducing migraine pain, obtaining a C grade of recommendation against this intervention ( Benatto et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current classification into grades of recommendation has shown that neck strengthening is not an effective intervention for migraine pain improvement, with a C grade of recommendation. Only one study evaluated the efficacy of neck strengthening in migraine treatment ( Benatto et al, 2022 ). If research in this field progresses, the grade of recommendation could change in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Page 2 of 12 Woldeamanuel and Oliveira The Journal of Headache and Pain (2022) 23:134 type of planned, structured, and repetitive movement/ physical activity performed to improve and/or maintain one or more components of physical fitness (e.g., aerobic fitness, muscle strength, etc.) [5,6] provides therapeutic effects on migraine [7][8][9][10]. Several clinical trials have demonstrated the efficacy of exercise interventions in the management of migraine [10][11][12][13][14][15][16].…”
Section: Open Accessmentioning
confidence: 99%
“…[5,6] provides therapeutic effects on migraine [7][8][9][10]. Several clinical trials have demonstrated the efficacy of exercise interventions in the management of migraine [10][11][12][13][14][15][16]. However, the exercise interventions involved different types of exercise modalities, i.e., aerobic exercise (highintensity aerobic exercise, moderate-intensity aerobic exercise), strength training, or even multimodal exercise training (i.e., aerobic, strength, flexibility) protocols [10][11][12][13][14][15][16][17].…”
Section: Open Accessmentioning
confidence: 99%
“…The data used from a study by Varkey et al included the mean differences in attack frequency instead of monthly migraine days [ 3 ]. Similarly, the data incorporated from another report by Benatto et al comprised the mean differences in headache frequency instead of monthly migraine days [ 4 ].…”
mentioning
confidence: 99%